1999
DOI: 10.1007/s005200050301
|View full text |Cite
|
Sign up to set email alerts
|

Quantity and quality of information desired by Portuguese cancer patients

Abstract: Disclosure of the diagnosis of cancer to the patients affected has always been a controversial issue in the doctor-patient relationship. Undoubtedly this is so not only because of differences between countries and cultures, but also because there have been changes of opinion over the years. The aim of this study was to evaluate the quality and quantity of information desired by Portuguese cancer patients, and how and from whom they want to hear this information. Our sample comprised a total of 193 cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 15 publications
1
28
0
8
Order By: Relevance
“…In Southern European countries, the area of physician-patient communication has been examined in terms of physicians' attitudes toward truthtelling with cancer patients (Arraras et al, 1995;Ferraz Gonc¸alves and Castro, 2001;Gil et al, 2000;, patients' awareness of their disease (Morasso et al, 1997;Mystadikou et al, 1996) and patients' desire for information during communication with their doctors (De Lorenzo et al, 2004;Pimentel et al, 1999). In contrast, no study in these countries has assessed the area of cancer physicians' communications skills, physicians' psychosocial orientation and the relationship between these two variables.…”
Section: Introductionmentioning
confidence: 99%
“…In Southern European countries, the area of physician-patient communication has been examined in terms of physicians' attitudes toward truthtelling with cancer patients (Arraras et al, 1995;Ferraz Gonc¸alves and Castro, 2001;Gil et al, 2000;, patients' awareness of their disease (Morasso et al, 1997;Mystadikou et al, 1996) and patients' desire for information during communication with their doctors (De Lorenzo et al, 2004;Pimentel et al, 1999). In contrast, no study in these countries has assessed the area of cancer physicians' communications skills, physicians' psychosocial orientation and the relationship between these two variables.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas indicam que 96% de pacientes ingleses (21) , 90% de americanos (22) e 85% de portugueses (23) gostariam de conhecer a verdade sobre a doença, bem como sobre as chances de cura (24,25) .…”
Section: Revelar Ou Não a Verdade Do Diagnósticounclassified
“…O médico, na grande maioria dos estudos, é o profissional que mais revela o diagnóstico aos pacientes (25,30,31) , pois é dele que os pacientes preferencialmente esperam receber a notícia (23,32) . No entanto, outros profissionais como, por exemplo, os enfermeiros vêm despontando nas preferências dos pacientes (5,21) .…”
Section: Quem Comunica O Diagnósticounclassified
“…In general, North American and Northern European populations expect more complete disclosure of information than Southern European populations (Perez-Stable et al, 1992;Mitchell, 1998;Galanti, 2000), although a survey of Portuguese-speaking cancer patients found that most of them desired full information (Pimentel et al, 1999). A survey comparing perceptions of cancer by people of Southern European origin (Latinos) and English speakers (Anglos) found that Latinos were more likely than Anglos to believe that having cancer is like getting a death sentence, and that they would prefer not to know if they had incurable cancer (Perez-Stable et al, 1992).…”
mentioning
confidence: 99%